Reported adverse drug reactions in public health facilities in Sabah: A cross-sectional study - LEONG, YI XIN; WAN ZAINAL RASHID, WAN ILI MUNIRAH; CHONG, GENEVIEVE ZHEN WUII; IZWANI ROSLI, NUR SYAKIRA (Malaysian Journal of Pharmaceutical Sciences, 2026)
Adverse drug reactions (ADRs) are among the major causes of death in many countries. ADR reporting is crucial to pharmacovigilance as it confers constant update on the safety of medicinal products. This study aimed to describe major causative therapeutic groups and common clinical manifestations of ADRs reported in public health facilities in Sabah. Data submitted to Malaysia Adverse Drug Reactions Advisory Committee (MADRAC) by public health facilities in Sabah from January to June 2022 were retrospectively reviewed. A total of 1,410 ADRs were included for analysis. Out of these, majority (80.2%, n = 1,131) were related to adults, while children constituted a notable proportion (12.7%, n = 180). More females (63%, n = 888) were involved than males. The West Coast Division reported the most ADRs (43.9%, n = 619) while Kudat Division reported the least number of ADRs (9.2%, n = 130). Anti-infectives for systemic use (48.5%, n = 684), in particular, penicillins (18.3%, n = 258), direct acting antivirals (9.6%, n = 136) and viral vaccines (6.5%, n = 91), were the most common contributors. Other common causative therapeutic groups were anti-inflammatory and anti-rheumatic products (10.9%, n = 153) and analgesics (6.9%, n = 97). Nirmatrelvir/Ritonavir (8.5%, n = 120) emerged as the most implicated drug, with a mean latency period of 14 hours, followed by amoxicillin (5.7%, n = 81) with a mean latency period of 27 hours. Skin and subcutaneous tissue disorders were the most common ADRs (45.7%, n = 644), with rash (n = 246), pruritus (n = 123), and swelling/oedema (n = 107) constituting the most common clinical manifestations. Severe cutaneous adverse reactions (SCARs) accounted for a minute proportion (0.64%, n = 9) of the analysed ADRs, wherein allopurinol (n = 3) was the most implicated causative drug. The minimal number (1.1%, n = 15) of reported drug rechallenges reflects inadequate implementation of allergy delabeling in Sabah.